Analysis of the Implementation of PSAK 46 on Report Quality Improvement Finance - Siti Fadhila Zanaria (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2023)
ABSTRACT.Application of PSAK 46 regarding the accounting treatment of income tax at PT. Rizki Cemerlang Transportaco is a good step to improve the quality of presentation of financial reports in order to make the right decisions. its financial statements refer to Financial Accounting Standards (SAK), so that the income reported in the income report is not necessarily the same as the profit value in accordance with tax regulations. Therefore, companies need to keep records of deferred tax in anticipation of the consequences of income tax (deferred tax assets and liabilities) both in the present and in the future. Deferred tax occurs when the current tax burden according to accounting is different from the current tax payable (tax payable in the current year according to tax regulations).